Evaluation of three novel retrograde filling materials (Microleakage study) (Mustansiria Dental Journal, 2018)
The aim of this study was to compare apical microleakage of MTA followingreverse retrograde root filling with that following Alumina Cement, Light Cement,Zenium HMP retrofilling. The root canals of 42 extracted teeth were instrumented andobturated with vertically condensed gutta-percha. Each tooth was apically resectedand the apex was prepared by fissure bur to 2 mm depth and the root surface isolatedwith nail varnish. Teeth were divided randomly into four groups of 10 teeth each.First group was retrofilled with MTA, second group with Alumina Cement, thirdgroup with Light Cement, and the fourth group with Zenium HMP. Followingimmersion in 2% Fuchsine dye for 72 hours, the roots were sectioned and the depth ofdye penetration was evaluated by a Global stereomicroscope at x70 magnification.Thesealing effectiveness of the retrograde filling materials was determined by their abilityto inhibit dye penetration. Results showed that the least leakage for zeniuum HMPcement with a mean of 0.6, MTA with a mean of 1.0, light cement with a mean of1.10, alumina cement with a mean of 1.50 with the most leakage. However, thesedifferences were not seen to be statistically significant using the Kruskal Wallis Testor the Mann Whitney Test. It was concluded that Zenium HMP cement provides abetter seal than MTA and Light Cement and Alumina Cement when used asretrograde filling.